Impact of Psycho-Educational Activities on Visual-Motor Integration, Fine Motor Skills and Name Writing among First Graders: A Kinematic Pilot Study - Livia Taverna; Marta Tremolada; Barbara Tosetto; Liliana Dozza; Zanin Scaratti Renata (MDPI AG, 2020)
This pilot study presents the effects on acquisition of pre-writing skills of educational activities targeting visual-motor integration and fine motor skills on a convenient sample of first graders. After a 10-week intervention program, visual perceptual skills and fine motor control were tested on 13 six-year-old aged children. Participants completed the Beery-Buktenica VMI and the manual dexterity scale of the Movement ABC-2 at baseline (T1), after the intervention program (T2), and one month after the end of the educational activities (T3). Children's writing pressure, frequency, and automaticity were measured using a digitizer during the administration of name writing test at T1, T2, and T3. The purpose of the study was to investigate changes in visual-perceptual abilities and fine motor skills after the intervention program and examine correlational effects on children's kinematic writing performances. Findings reveal that educational activities impacted positively on children's visual motor coordination component of writing improving VMI scores. No statistically significant difference was detected across the three time points on students' manual dexterity skills. Measurement of writing kinematics allows to report and document variations in children's writing during intervention. This pilot study discusses these findings and their implications for the field on early childhood acquisition of foundational skills for handwriting. It also proposes potential topics for future research on this field.